Noncoding translation: Quality control in the BAG - Mohsen, Jessica J.; Slavoff, Sarah A. (Molecular cell, 2023)
Translation of noncoding regions is ubiquitous and upregulated in disease. Kesner et al.1 elucidate the mechanism by which the BAG6 complex exerts quality control over noncoding translation while targeting stable, noncanonical polypeptides to cellular membranes. Translation of noncoding regions is ubiquitous and upregulated in disease. Kesner et al.1 elucidate the mechanism by which the BAG6 complex exerts quality control over noncoding translation while targeting stable, noncanonical polypeptides to cellular membranes.